Dampak Pandemi Covid-19 Terhadap Pengguna Jasa Pegadaian Syariah Pasar Singkut Sarolangun - Salman Alparisi; Arsa Arsa; Bambang Kurniawan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to determine the impact of the Covid-19 pandemic on service users at PT. Pawnshop Sharia Sarolangun short market. This research is a qualitative descriptive study, with data collection methods namely interviews, observation and documentation and using data analysis techniques namely data reduction, data presentation and drawing conclusions. Informants in this study are employees and customers who are involved. The results of this study indicate that the covid-19 pandemic has had little impact on service users at PT. Pegadaian Syariah Pasar Singkut Sarolangun, this is because during the covid-19 pandemic many people were less stable in the economy which was caused by several policies set by the government in order to eradicate the spread of the covid-19 virus. PT. Pegadaian Syariah Pasar Singkut Sarolangun provides the best possible effort to provide good service and in accordance with health procedures that have been established during the Covid-19 pandemic. This can be seen from the several dimensions that have been described, namely security, service quality, guarantees provided and employee responsiveness which is always paid attention to by PT. Sharia Pegadaian Pasar Singkut Sarolangun.